2005
DOI: 10.1111/j.1365-2486.2005.00984.x
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated belowground C cycling in a managed agriforest ecosystem exposed to elevated carbon dioxide concentrations

Abstract: We investigated the effects of three elevated atmospheric CO 2 levels on a Populus deltoides plantation at Biosphere 2 Laboratory in Oracle Arizona. Stable isotopes of carbon have been used as tracers to separate the carbon present before the CO 2 treatments started (old C), from that fixed after CO 2 treatments began (new C). Tree growth at elevated [CO 2 ] increased inputs to soil organic matter (SOM) by increasing the production of fine roots and accelerating the rate of root C turnover. However, soil carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(102 citation statements)
references
References 72 publications
6
93
0
3
Order By: Relevance
“…However, recent studies have shown the importance of soil C availability as a driver of heterotrophic respiration (Vance and Chapin, 2001;Trueman and Gonzalez-Meler, 2005;Scott-Denton et al, 2006). There is evidence that fresh C input into soil can increase, decrease or have little or no effect on R h Fontaine et al, 2007).…”
Section: Rhizosphere Respirationmentioning
confidence: 99%
“…However, recent studies have shown the importance of soil C availability as a driver of heterotrophic respiration (Vance and Chapin, 2001;Trueman and Gonzalez-Meler, 2005;Scott-Denton et al, 2006). There is evidence that fresh C input into soil can increase, decrease or have little or no effect on R h Fontaine et al, 2007).…”
Section: Rhizosphere Respirationmentioning
confidence: 99%
“…First, we hypothesized that more diverse systems would have greater TBCA because complementary resource use results in greater C fixation and productivity (Tilman and others 1996;Fargione and others 2007). Second, we hypothe-sized that because root production, respiration, exudation, and mycorrhizal allocation tend to increase at elevated CO 2 , likely due to increased photosynthate availability (Matamala and Schlesinger 2000;Treseder and Allen 2000;Pendall and others 2004;Allen and others 2005;Trueman and Gonzalez-Meler 2005), TBCA would increase at elevated CO 2 . However, over time, the CO 2 fertilization effect may create feedbacks that reduce N availability and thus also reduce the stimulation of biomass by elevated CO 2 (progressive N limitation, PNL; Reich and others 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of δ 13 C in respiratory CO 2 showed that, rather than the anticipated increase of soil sequestration of carbon (163), stimulation of aboveground carbon influx by elevated [CO 2 ] actually primed respiration of residual soil carbon (164), without significantly altering the soil microbial biota (82). Among other things, leaf-canopy-ecosystem experiments in B2L made a unique contribution to the debate about the CO 2 sequestration capacity of fast-growing woody plants to mitigate increasing atmospheric [CO 2 ].…”
Section: The Plantation Forest Mesocosmmentioning
confidence: 99%